The Role of Xenobiotic-Metabolizing Enzymes in Anthelmintic Deactivation and Resistance in Helminths - Matoušková, Petra; Vokřál, Ivan; Lamka, Jiří; Skálová, Lenka (Trends in parasitology, 2016)
Xenobiotic-metabolizing enzymes (XMEs) modulate the biological activity and behavior of many drugs, including anthelmintics. The effects of anthelmintics can often be abolished by XMEs when the drugs are metabolized to an inefficient compound. XMEs therefore play a significant role in anthelmintic efficacy. Moreover, differences in XMEs between helminths are reflected by differences in anthelmintic metabolism between target species. Taking advantage of the newly sequenced genomes of many helminth species, progress in this field has been remarkable. The present review collects up to date information regarding the most important XMEs (phase I and phase II biotransformation enzymes; efflux transporters) in helminths. The participation of these XMEs in anthelmintic metabolism and their possible roles in drug resistance are evaluated.
Keywords: proteiny červů; interakce hostitele a parazita; Helminth Proteins; Drug Resistance; Anthelmintics; Helminths; detoxification; genom u helmintů; anthelmintika; zvířata; Genome, Helminth; cizopasní červi; drug resistance; drug transport; léková rezistence; Host-Parasite Interactions; drug biotransformation; Animals